Screening for and Verification of Novel Mutations Associated with Drug Resistance in the HIV Type 1subtype B′ in China - Li, Hanping; Geng, Qingmao; Guo, Wei; Zhuang, Daomin; Li, Lin; Liu, Yongjian; Bao, Zuoyi; Liu, Siyang; Li, Jingyun (PLOS ONE, 2012)
Objective Mutations associated with HIV drug resistance have been extensively characterized at the HIV-1 polymerase domain, but more studies have verified that mutations outside of the polymerase domain also results in resistance to antiviral drugs. In this study, mutations were identified in 354 patients experiencing antiretroviral therapy (ART) failure and in 97 naïve-therapy patients. Mutations whose impact on antiviral drugs was unknown were verified by phenotypic testing. Methods Pol sequences of HIV subtype B′ obtained from patients experiencing ART failure and from naïve-therapy patients were analyzed for mutations distinct between two groups. Mutations that occurred at a significantly higher frequency in the ART failure than the naïve-therapy group were submitted to the Stanford HIV Drug Resistance Database (SHDB) to analyze the correlation between HIV mutations and drug resistance. For mutations whose impact on the antiviral drug response is unknown, the site-directed mutagenesis approach was applied to construct plasmids containing the screened mutations. 50% inhibitory concentration (IC50) to AZT, EFV and NVP was measured to determine the response of the genetically constructed viruses to antiviral drugs. Results 7 mutations at 6 positions of the RT region, D123E, V292I, K366R, T369A, T369V, A371V and I375V, occurred more frequently in the ART failure group than the naïve-therapy group. Phenotypic characterization of these HIV mutants revealed that constructed viruses with mutations A371V and T369V exhibited dual resistance to AZT and EFV respectively, whereas the other 5 mutations showed weak resistance. Although the impact of the other six mutations on response to NVP was minimal, mutation T369V could enhance resistance to NVP. Conclusions This study demonstrated that mutations at the RT C-terminal in subtype B′ could result in resistance to RT inhibitors if the mutations occurred alone, but that some mutations could promote susceptibility to antiviral drugs.